Hypertension In Pregnancy: A Review of Preecamplesia,Its Effects and Management - Shama Chaudhry; Rubina Hussain (ziauddin University, 2024)
ABSTRACT Hypertension complicates 5% to 7% of all pregnancies Pre-eclampsia is a major contributor to maternal mortality worldwide. In Africa and Asia they contribute to 9% of deaths. A subset of preeclampsia, characterized by new-onset hypertension, proteinuria, and multisystem involvement, is responsible for substantial maternal and fetal morbidity and is a marker for future cardiac and metabolic disease. It is a pregnancy-specific disease characterized by de-novo development of concurrent hypertension and proteinuria, sometimes progressing into a multi organ cluster of varying clinical features. Poor early placentation is especially associated with earl y onset disease. Symptomatic clinical management should be mainly directed to prevent maternal morbidity (e.g. eclampsia) and mortality. Expectant management of women with early onsetdisease to improveperinatal outcome should not preclude timely delivery-the only definitive cure. KEY WORDS: Proteinuria, Preeclampsia, Uteroplacenial, Glomerular Endotheliosis.